Improve English Language Skills through Meeting Training Vocabulary (MTV) for Ban Khlongrua School Krabi Thailand Students (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This study aims to evaluate the success of training programs in enriching students' vocabulary and encouraging the use of English as a second language. The methods used in this program involve an interactive approach and actively involve students. Training is conducted with a focus on vocabulary that is relevant and useful in everyday life. Evaluation is done through direct observation, written tests, and feedback from the students and teachers involved. The results showed that the English vocabulary training program has given positive results. Students show significant improvement in the understanding and use of new vocabulary. The motivation of students in learning English also increases, which is reflected in their active participation in training activities. In addition, the program provides long-term benefits to students at Ban Khlongrua School Krabi, Thailand. By mastering English as a second language, students can be better prepared to face global challenges and expand future educational and career opportunities. In addition, strong English language skills also contribute to the formation of students' cultures and perspectives, opening doors for cross-cultural cooperation and better understanding between students of Ban Khlongrua School Krabi, Thailand and students from different countries of the world. In order to continue the programme, it is important to maintain continuity and involve all relevant stakeholders. Continuous training and regular updating of learning materials need to be held so that students continue to acquire new vocabulary knowledge relevant to their needs.